Perceived risks, challenges and coping strategies among West African immigrant entrepreneurs in Ghana - Elijah Yendaw; Linus Baatiema; Edward Kwabena Ameyaw (Heliyon, 2023)
Globally, immigrants’ entrepreneurship has been widely acknowledged as a critical driver for the socio-economic development of nations. Yet, studies barely examine the risks and difficulties immigrants encounter in their business transactions, especially those engaged in small-scale itinerant retail businesses. This paper strives to fill this lacuna from the contextual perspective of the Global South by examining the risks and complexities of West African immigrant entrepreneurs in Accra, Ghana. This paper draws data from a survey of 779 respondents and in-depth interviews with nine key informants. The data from the survey were analysed using descriptive statistics (e.g., bivariate analysis) whilst the qualitative data were analysed thematically. The study indicates that work-related health hazards and accommodation difficulties are the main risks and difficulties immigrants encounter in their everyday business operations. Additionally, fatigue ensuing from excessive trekking, and exposure to the scorching sun are the specific health risks associated with their business. Coping strategies of immigrant entrepreneurs included resorting to support from family and friends in Ghana and back home. Others included reliance on their skills/expertise to earn a living, self-medication-usually pain killers intended to overcome fatigue, relying on migrant networks and doing other menial jobs. The findings suggest that whilst the business operations of the immigrant entrepreneurs offer possibility to eke a living, diverse risk factors and complexities counter the efforts of the immigrant retailers. The paper recommends that leadership of the immigrant groups should organise health education programs for their members towards ensuring that immigrant entrepreneurs adopt health safety practices such as limiting exposure to scorching sun, excessive fatigue and unsupervised self-medication.